2019
DOI: 10.1111/cogs.12706
|View full text |Cite
|
Sign up to set email alerts
|

“I Want to Know More!”: Children Are Sensitive to Explanation Quality When Exploring New Information

Abstract: When someone encounters an explanation perceived as weak, this may lead to a feeling of deprivation or tension that can be resolved by engaging in additional learning. This study examined to what extent children respond to weak explanations by seeking additional learning opportunities. Seven‐ to ten‐year‐olds (N = 81) explored questions and explanations (circular or mechanistic) about 12 animals using a novel Android tablet application. After rating the quality of an initial explanation, children could request… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 42 publications
(64 reference statements)
2
18
0
Order By: Relevance
“…Do preschool children explore because they are systematically trying to reduce uncertainty or maximize long-run rewards, or simply because they like to make new things happen, or are noisy and impulsive? Earlier studies have shown that children's exploration reflects their understanding (L. E. Schulz & Bonawitz, 2007;Bonawitz et al, 2012;Cook et al, 2011;Legare, 2012;Mills et al, 2019;Stahl & Feigenson, 2015), and this is consistent with our findings that children behaved differently depending on what they had learned (Study 4), and changed their behavior across trials (Studies 2-3). This suggests that children's exploration is not solely the result of noise or impulsiveness (see also Blanco & Sloutsky, 2019, 2020Sumner, Steyvers, et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Do preschool children explore because they are systematically trying to reduce uncertainty or maximize long-run rewards, or simply because they like to make new things happen, or are noisy and impulsive? Earlier studies have shown that children's exploration reflects their understanding (L. E. Schulz & Bonawitz, 2007;Bonawitz et al, 2012;Cook et al, 2011;Legare, 2012;Mills et al, 2019;Stahl & Feigenson, 2015), and this is consistent with our findings that children behaved differently depending on what they had learned (Study 4), and changed their behavior across trials (Studies 2-3). This suggests that children's exploration is not solely the result of noise or impulsiveness (see also Blanco & Sloutsky, 2019, 2020Sumner, Steyvers, et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Our focus on the delivery of scientific content is consistent with research indicating that children are not only sensitive to the content of information when making inferences about from whom to learn but are also sensitive to the manner in which that content is delivered (Corriveau and Kurkul, 2014;Mercier et al, 2014;Kurkul and Corriveau, 2018;Mills et al, 2019). Specifically, we explore delivery of scientific content via two different pedagogical approaches they could use when participating in a scientific activity with their child.…”
Section: The Role Of Parental Explanations In Early Science Learningmentioning
confidence: 60%
“…These approaches depend highly on the user's expertise and established vocabulary that form a basis for revealing relevant underlying causes and relationships. As already mentioned, the terms have evolved from research on scientific explanations and refer to an explainee experiencing a specific knowledge gap [44]. However, in natural interactions, the explanans and explanandum might be underspecified or not defined at the beginning of an interaction.…”
Section: Dynamics Of Understandingmentioning
confidence: 99%